The factor that affecting customer satisfaction in insurance Prudential BSN Takaful / Nur Eylia Razali and Nurfatin Abdul Karim - Razali, Nur Eylia; Abdul Karim, Nurfatin (2013)
The research paper is about a study on the factors that are affect customer satisfaction in Insurance Prudential BSN Takaful. The objectives of this study are to measure the level of customer satisfaction and service quality of Insurance Prudential BSN Takaful customers and to investigate the relationship between customer satisfaction and SERVQUAL dimensions which are tangible, reliability, responsiveness, assurance, and empathy among Insurance Prudential BSN Takaful. In this study, the primary and secondary data will be used. this is including the interview, questionnaires, journals, books and articles. Method that has been used to analyze the data that have been gathered is reliability test, descriptive analysis and pearson correlation. In the end of this study, the researcher conclude that the level of customer satisfaction in Insurance Prudential BSN Takaful and service quality is high and there are significant relationship between customer satisfaction and service quality dimensions which are tangible, reliability, responsiveness, assurance and empathy among customer Insurance Prudential BSN Takaful.